Quantifying the impact of a constructed wetland on downstream nitrate concentrations and loads in the U.S. Midwest - Anderson, Elliot; Schilling, Keith E.; Just, Craig L.; Seo, Bong Chul (Frontiers in Environmental Science, 2024)
Constructed wetlands are standard conservation practices used to reduce nitrate loads in agricultural watersheds. Many studies have examined the efficiency of denitrification in wetlands under various scenarios, but quantifying the watershed-scale impact of wetlands on downstream nitrate levels is rarely done using field observations. In this study, we estimated nitrate removal in a constructed wetland in the headwaters of Mud Creek, a HUC12 watershed in eastern Iowa, from May -Sep 2022 and May -Sep 2023 (a ten-month period). We also measured nitrate loads at four successive downstream sites, three along Mud Creek and one below its confluence with the larger Cedar River. The wetland removed 6,200 kg of nitrate (74% of total inputs). At the three downstream locations in Mud Creek, the percentage of each site's total nitrate load removed by the wetland decreased to 19, 8.6, and 4.1%-this latter value represents the wetland's influence on nitrate removal in the entire Mud Creek basin. The wetland's impact of nitrate loads in the Cedar River was negligible (reduction of 0.02%). The percentage of a site's drainage area treated by the wetland approximately followed a 1:1 relationship to that site's percent reduction in nitrate. Profiles of nitrate concentrations in Mud Creek notably varied preand post-wetland. Concentrations before the installation steadily decreased along the waterway, while post-wetland concentrations rapidly decreased directly downstream of the wetland and steadily increased at each succeeding site. Our results demonstrate that while the wetland successfully lowered local nitrate levels, its effect on the basin's overall nitrate loads was minimal. Achieving nutrient reduction goals at the watershed scale solely using constructed wetlands appears infeasible given that the required number of practices greatly exceeds current efforts.